Recreational Health Activities of Pregnant Women Attending Ante Natal Clinics in Etinan - ATARE, Franz U.; Ekpu, Felicia S. (Advances in Social Sciences Research Journal, 2021)
AIM: The study sought to assess the practice, awareness, adherence, benefits and promotion of Recreational Health Activities by pregnant women attending ante natal care clinics in Etinan. METHOD: The survey research design was adopted for the study. 180 pregnant women out of the 536 registered and undertaking antenatal care in Primary Health Centres were selected by stratified random sampling. Self-structured questionnaire validated by experts and subjected to a reliability test with a coefficient of .68 was used for data collection. RESULTS: The study revealed that majority of pregnant women in Etinan were not practicing recreational health activities though they expressed awareness of the activities. They do not adherence to recommended activities by care givers and thus did not benefit from it. CONCLUSION AND RECOMMENDTIONS: It was recommended that pregnant women should be encouraged to participate in regular recreational activities before, during and after delivery so that they can adhere during future pregnancy. Couple days’ should be incorporated into ante natal care programmes so husbands will have an opportunity of taking part in recreational health activities with their pregnant wives.